Green technology in green macroalgal biorefineries. Issue 5 (3rd September 2019) - Zollmann, Meiron; Robin, Arthur; Prabhu, Meghanath; Polikovsky, Mark; Gillis, Amichai; Greiserman, Semion; Golberg, Alexander
ABSTRACT: Marine biorefineries, based on macroalgal (seaweed) feedstocks, could provide sustainable alternative sources of food, energy, and materials. Green macroalgae, with their unique chemical composition, can contribute to marine biorefinery systems associated with a wide range of potential products. This review discusses the challenge of developing industrially relevant and environmentally-friendly green seaweed biorefineries. First, we review potential products from green seaweeds and their co-production, the key element in an integrated biorefinery. Second, we discuss large-scale cultivation, hydrothermal treatments, fermentation, anaerobic digestion, and emerging green solvents, pulsed electric field, microwave, and ultrasound processing technologies. Finally, we analyse the main polysaccharides in green seaweeds: sulfated polysaccharides, starch, and cellulose, as products of a cascading biorefinery, with emphasis on applications and technological challenges. We provide a comprehensive state-of-the-art review of green seaweed as feedstock for the biorefinery, analysing opportunities and challenges in the field.